VILLAGE FUNDS UTILIZATION STRATEGY TO IMPROVE FOOD SECURITY IN KUWU VILLAGE, DEMPET SUB-DISTRICT, DEMAK REGENCY - Yuliana, Intan (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2019)
The aim of this study was to analyze food security improvement strategy in line with the potency and problems, so that the utilization of village funds is more optimal and on target in order to support the financing of food security in Kuwu village, Dempet Sub-district, Demak Regency. The type of this research is quantitative research by using SWOT analysis. This research used primary and secondary data. The results of analysis showed that the utilization of Kuwu Village Fund was more concerned with physical development as well as transportation facilities and infrastructure. The results of SWOT analysis showed that the appropriate strategy to improve food security through the use of Village Funds in Kuwu Village is to support aggressive growth policy by maximizing the strengths and opportunities such as increasing food production capacity by intensification and diversification, human resource development, and improving the road infrastructure of farmer business.